The Evolution of Intelligent Systems - Richardson, K. author. aut Link
IX, 234 p.
Keywords: How could something as seemingly transcendental as the human mind have arisen from far simpler material beginnings? This book provides a comprehensive overview of evolution from pre-life and early life forms through increasing complexity to advanced cognitive systems using a new framework based on dynamic systems theory.